New faiths, old fears : Muslims and other Asian immigrants in American religious life - Lawrence, Bruce B. (New York : Columbia University Press, 2002)
As a result of immigration from Asia in the wake of the passage of the 1965 Hart-Celler Immigration Act, the fastest-growing religions in America -- faster than all Christian groups combined -- are Islam, Hinduism, Buddhism, and Sikhism. Now a leading scholar asks how these new faiths have changed or have been changed by the pluralist face of American civil society and by the deep-rooted American ambivalence toward foreign traditions.
Table of Contents -- Preface -- Introduction -- 1. American Religion as Commodity Culture -- 2. Civil Society and Immigrants -- 3. New Immigrants as Pariahs -- 4. Religious Options for Urban Immigrants -- 5. Reimagining Religious Pluralism -- Conclusion -- Notes -- Selected Bibliography -- Index
Includes bibliographical references (pages 179-186) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: United States -- Religion -- 1945-; Asians -- United States -- Religion; Immigrants -- Religious life -- United States -- History -- 20th century; États-Unis -- Religion -- 1945-; Asiatiques -- États-Unis -- Religion; 11.84 Islam: other; RELIGION -- Religious Intolerance, Persecution & Conflict; RELIGION -- Islam -- History; Asians -- Religion; Immigrants -- Religious life; Religion; United States; Asiaten; Muslim; Religiöses Leben; USA; Religion; Multikulturelle Gesellschaft; Muslims; Immigrants; Religion; United States; Kulturell assimilation -- religiösa aspekter -- Förenta staterna; Förenta staterna -- asiatiska influenser; Asiaten; Since 1900; History